Enhancing regenerative medicine: the crucial role of stem cell therapy - Wang, Jipeng; Deng, Gang; Wang, Shuyi; Li, Shuang; Song, Peng; Lin, Kun; Xu, Xiaoxiang; He, Zuhong (Frontiers in Neuroscience, 2024)
Stem cells offer new therapeutic avenues for the repair and replacement of damaged tissues and organs owing to their self-renewal and multipotent differentiation capabilities. In this paper, we conduct a systematic review of the characteristics of various types of stem cells and offer insights into their potential applications in both cellular and cell-free therapies. In addition, we provide a comprehensive summary of the technical routes of stem cell therapy and discuss in detail current challenges, including safety issues and differentiation control. Although some issues remain, stem cell therapy demonstrates excellent potential in the field of regenerative medicine and provides novel tactics and methodologies for managing a wider spectrum of illnesses and traumas.